BACTERIOLOGICAL PROFILE AND ANTIBIOGRAM OF GRAM-NEGATIVE BACILLI ISOLATED FROM ENDOTRACHEAL TUBE SECRETIONS AND TRACHEAL ASPIRATES FROM PATIENTS ON MECHANICAL VENTILATION: A HOSPITAL-BASED CROSS-SECTIONAL STUDY - SNEHITHA, K.; SWAPNA, S.; KAMALA, P. (International Journal of Current Pharmaceutical Research, 2024)
Objective: Nosocomial infections have become a serious threat to mortality and morbidity among hospitalized patients. Major risk factor among critically ill patients is excessive use of invasive devices like Endotracheal tube (ET) and tracheal intubation. The development of biofilm and their subsequent dislodgement aids in lung colonization and may cause Ventilator-associated pneumonia (VAP) [1]. Methods: Present study was conducted on ET tube tips and Tracheal aspirates received in microbiological laboratory from various ICU’s (Medical, surgical and pediatric) in Andhra Medical College, Visakhapatnam over a period of one year from September 2022 to August 2023. A total of 116 samples were processed according to standard protocols and Antibiotic Susceptible Testing (AST) was performed by Kirby-Bauer disc diffusion method on Mueller-Hinton agar as per CLSI guidelines. Results: In total, 116 samples were processed. ET tube tips were 76/116 and tracheal aspirates were 40/116, with males (69/116) outnumbered females (47/116). Out of a total of 116 samples, 72 (62%) were culture-positive and 44 (38%) were sterile. Acinetobacter spp. was the most common pathogen among 72 culture positives (31/72, 43%), followed by Klebsiella spp. (20/72, 28%), Pseudomonas spp. (13/72, 18%) and Escherichia coli (8/72, 11%). A total of 11 (11/72, 15%) GNB were found as multi-drug resistant. The multi-drug resistant GNB isolated were Acinetobacter (6/72), Klebsiella (3/72) and Pseudomonas (2/72). Meropenem is the most susceptible antibiotic, followed by Piperacillin-Tazobactam. Conclusion: It was concluded from this study that most commonly isolated pathogen was Acinetobacter spp. Most of these isolates were sensitive to Carbapenem and BLBLI combination drugs. Microbial persistence and impaired response to the treatment were more frequent, when multi-drug resistant organisms were present. Hence a local combined antibiotic approach, based on bacteriological profile and AST is essential to initiate empirical therapy which will minimize the bacterial colonization and prevent the incidences of VAP.